Lunar phobia in the greater fishing bat Noctilio leporinus (Chiroptera: Noctilionidae) - S. Börk, Karrigan (2006)
The nightly activity patterns of Noctilio leporinus, a piscivorous neotropical bat, were documented by visual observation over one lunar cycle at a large dock in Golfito, Costa Rica. The activity patterns were compared to the intensity of the moonlight, and a strong correlation between darkness and activity was observed (n = 776, r2 = 0.96). This correlation has been observed in many species of mammals and may indicate adaptation by potential prey species to avoid predation by visually oriented nighttime predators and/or an adaptation by predators to maximize hunting success.